2021
DOI: 10.1002/ejoc.202101064
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Addition of Sodium Bisulfite to Nitroalkenes. A Convenient Approach to Chiral Sulfonic Acids

Abstract: An enantioselective organocatalytic addition of sodium bisulfite to (E)‐nitroalkenes has been developed by using a chiral bifunctional organocatalyst. The present methodology provides a variety of chiral β‐nitroethanesulfonic acid compounds (17 examples) with excellent results: up to 99 % yield and excellent enantioselectivity (up to 96 % ee). The reaction tolerates (hetero)aryl and alkyl substituents on the β‐nitroalkenes, and β,β‐disubstituted nitroalkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Recently, Sheikhi et al demonstrated the potential of sodium bisulfite (NaHSO 3 ) as a new sulfur-based nucleophile for enantioselective organocatalytic conjugate addition to β-nitrostyrene derivatives. [60] The reaction was efficiently conducted in the presence of a Takemoto-type bifunctional thiourea catalyst (Cat-27), yielding excellent catalytic results. Notably, the reaction smoothly proceeded even in the case of β,βdisubstituted nitroalkene.…”
Section: Sulfur-based Nucleophiles In Conjugate Addition Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sheikhi et al demonstrated the potential of sodium bisulfite (NaHSO 3 ) as a new sulfur-based nucleophile for enantioselective organocatalytic conjugate addition to β-nitrostyrene derivatives. [60] The reaction was efficiently conducted in the presence of a Takemoto-type bifunctional thiourea catalyst (Cat-27), yielding excellent catalytic results. Notably, the reaction smoothly proceeded even in the case of β,βdisubstituted nitroalkene.…”
Section: Sulfur-based Nucleophiles In Conjugate Addition Reactionsmentioning
confidence: 99%
“…[5] The β‐nitro compounds with quaternary stereocenters formed via conjugate addition to β,β‐disubstituted nitroalkenes can be easily transformed into several important species such as β 2,2 ‐amino acids and γ‐aminobutyric acids (GABAs) [6,7,8] . Therefore, the past few decades have witnessed the extensive development of catalytic asymmetric conjugate additions to β,β‐disubstituted nitroalkenes and the emergence of the corresponding elegant strategies [9–60] …”
Section: Introductionmentioning
confidence: 99%
“…2021 年, Blay 课题组 [94] 和 Brière 课题组 [95] 先后报道 了亚硫酸氢钠对 β-硝基苯乙烯在不同硫脲催化下的立 体选择性加成反应, 并以优异产率和对映选择性获得了 相应的 β-硝基磺酸衍生物(Eq. 47).…”
Section: β-硝基烯烃和醛被各种催化剂催化得到相应加成unclassified
“…16,18,19,39,45 As far as we know, synthesis of sulfonate gemini surfactants using natural linoleic acid as building blocks is rarely reported. Inspired by the reported work on organocatalyzed addition of NaHSO 3 to α,β-unsaturated alkenes by employing organic base catalysis [46][47][48][49][50] as well as our previous work on sulfonation of alkyl oleate with NaHSO 3 catalyzed by the TBPB/iron (III) chloride (FeCl 3 ) system, 32 we initiated our investigation on the synthesis of sulfonate gemini surfactants through the addition of NaHSO 3 to alkyl linoleate so as to find appropriate conditions using MLO as a model substrate Notably, SMLD was detected as the only product with varying the reaction time (Figure S7). Hence, 20 h was chosen as the optimal reaction time.…”
Section: Optimization Of Sulfonation Reaction Conditionsmentioning
confidence: 99%